2020
DOI: 10.20944/preprints202009.0551.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soil Nutrients and Carbon Dynamics in the Presence of Biochar-swine Manure Mixture Under Controlled Leaching Experiment Using a Midwestern USA Soil

Abstract: Biochar application to the soil can improve soil quality and nutrient leaching loss. Recent studies have reported that surficial application of biochar to stored swine manure can reduce emissions of odorous compounds and reduce the volatilization loss of ammonia. Our working hypothesis was that the biochar-treated manure application to the soil would decrease nutrient leaching from manure and increase plant-available nutrients. The study objectives were to evaluate the impact of biochar-treated swine manure on… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
2
2
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…However, the impact of these manure additives such as (biochar, soybean peroxide) still needed further research on larger scales and farms with different manure management systems. Most recently, research has shown that biochar-treated manure can have beneficial agronomic effects, as reported by Banik et al (2020). There is an early indication that biochar-manure mixture has the potential to further improve the nitrogen and carbon cycling and sustainability of animal and crop production.…”
Section: Discussionmentioning
confidence: 95%
“…However, the impact of these manure additives such as (biochar, soybean peroxide) still needed further research on larger scales and farms with different manure management systems. Most recently, research has shown that biochar-treated manure can have beneficial agronomic effects, as reported by Banik et al (2020). There is an early indication that biochar-manure mixture has the potential to further improve the nitrogen and carbon cycling and sustainability of animal and crop production.…”
Section: Discussionmentioning
confidence: 95%
“…The plant-available P and K [34] and other plant micronutrients were extracted by Mehlich-3 [35][36][37] and analyzed by ICP-OES. The details of the incubation and data for biochar, manure, and manure-biochar mixtures were reported elsewhere [20].…”
Section: Soil Collection Biochar Manure and Manure-biochar Incubationmentioning
confidence: 99%
“…These observations have also prompted surface-modified biochar research to enhance the sorption of oxyanions onto biochar surfaces via complexation and ligand exchange reactions to develop P removal or release strategies [16][17][18][19]. We recently reported that surface-modified Fe-biochar application also showed low soil heavy metal concentrations without compromising crucial plant-available soil nutrients upon manure application [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, biochar can be used to mitigate emissions from manure while adsorbing nutrients from manure and, at the same time, preventing losses to the atmosphere. Banik et al (2020) reported that using biochar and manure mixture significantly increased the organic matter, total carbon (C), and total N of the soil. Therefore, we propose to use biochar treatment to improve air quality inside barns, improve worker and animal safety during manure agitation (e.g., Chen et al, (2020b), and to valorize biochar-treated manure.…”
Section: Effect On Volatile Organic Compoundsmentioning
confidence: 99%